A new species of Bertolonia (Melastomataceae) from southern Bahia, Brazil - Bacci, Lucas F.; Amorim, André M.; Michelangeli, Fabián A.; Goldenberg, Renato (Phytotaxa, 2016)
We describe and illustrate Bertolonia hirsutissima, a new species from the state of Bahia in Brazil. It has been collected only three times in one locality in the municipality of Wenceslau Guimarães. The new species can be recognized by the combination of bullate/foveolate leaf surfaces, hirsute petioles (these also with sessile and stalked glands), long sepals with crenulate-denticulate and long ciliate margins, and anthers lacking appendages and dehiscing through an extrorse apical pore.